2021
DOI: 10.1371/journal.pntd.0009757
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal schistosomiasis among schoolchildren in Sana’a Governorate, Yemen: Prevalence, associated factors and its effect on nutritional status and anemia

Abstract: Intestinal schistosomiasis is a neglected tropical disease, causing morbidity and mortality in tropical and subtropical countries. Despite the frequent implementation of mass drug administration with praziquantel, the reinfection with Schistosoma mansoni is still common in Yemen. In addition, there is a scarcity of information on the impact of S. mansoni on nutritional status and anemia among schoolchildren. The present study aimed to determine prevalence and risk factors of intestinal schistosomiasis and inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Lack of district anaemia data from 2010 precluded any estimation of the impact of the NSCP on the prevalence of anaemia. A Master’s thesis conducted in 2018 explored the prevalence of intestinal SCH and its effect on nutritional status and anaemia among schoolchildren in two districts in Sana’a Governorate [ 46 ]. The study demonstrated that the highly focal distribution of intestinal SCH was related to prevalence of wasting and stunting in early adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of district anaemia data from 2010 precluded any estimation of the impact of the NSCP on the prevalence of anaemia. A Master’s thesis conducted in 2018 explored the prevalence of intestinal SCH and its effect on nutritional status and anaemia among schoolchildren in two districts in Sana’a Governorate [ 46 ]. The study demonstrated that the highly focal distribution of intestinal SCH was related to prevalence of wasting and stunting in early adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in Africa and elsewhere on populations of similar age have shown the following Anemia in 3 months to 6 years old Children infected with S. mansoni and intestinal Protozoans prevalences: in Ethiopia, 24.6% of S. mansoni and 15.4% of anemic [33]; in Uganda 71.0% S. mansoni infection and anemia not evaluated [24], and in India reaching 33.9% S. mansoni and anemia at 31.7% [34] (Al-Haidari et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…In 2021, 159 million school-aged children living in Africa will require preventive chemotherapy for STH [5]. Previous studies suggested high prevalence of schistosomiasis and undernutrition, such as wasting, stunting, or anemia, and their associations among school-aged children in sub-Saharan Africa [8][9][10][11][12]. Thus, the prevention of these parasitic diseases in school-aged children is an urgent challenge.…”
Section: Introductionmentioning
confidence: 99%